Investigating the Trypanocidal Activity of Purified Precocene I by Reverse-Phase High-Performance Liquid Chromatography from Essential Oil of Ageratum houstonianum Aerial Parts - P. Shaba; N. N. Pandey; O. P. Sharma; N. N. Pandy; J. R. Rao; S. Dey; B. D. Mandal; N. P. Kurade; R. K. Singh; V. Bhanuprakash; et al. (Technological Innovation in Pharmaceutical Research Vol. 10, 2021)
Ageratum houstonianum leaves are a common poisonous weeds found on the vast valley of Kangra in Palampur, Himachal Pradesh State, India. Freshly harvested leaves sample of Ageratum houstonionum were dried under shade and powdered. Leaf sample of A. houstonionum was extracted by process of hydrodistillation using a Clevenger-type apparatus for the preparation of essential oil. Extract from A. houstonianum was prepared by dissolving 5 µL of the essential oil in 10 mL methanol. All the sample was filtered through a Whatman (Maidstone, England) stainless steel syringe assembly using a 0.22 µm Durapore (Millipore: Milford, USA) membrane filter. Purification processes via column chromatography, thin layer chromatography and preparative thin layer chromatography were done. Reverse phase HPLC analysis was carried out via a Waters HPLC system consisting of model 510 and 515 pumps, a Rheodyne injector, a Novapak C18 column (250 x 4.6 mm i.d.; 4 µm), a model 490E multi-channel detector and Millennium 2010 sata manager. The mobile phase constituents were filtered using a Durapore 0.22 µm membrane filter. The elution was carried out with a linear gradient of acetonitrile: water (40:60) to pure acetonitrile in 60 min at a flow rate of 1 mL/min. detection was at 210, 240, 280 and 320 nm. The precocene was eluted within 25 min, the peak areas showed good reproducibility (average relative standard deviation were 0.78%), and the calibration curves (i.e. mass of precocene standard injected vs. peak area detected at 210 nm) were linear over the range of 0.05-10 µg (for precocene I, y = 6654454 x + 176626, r2 = 0.99 and for precocene II, y = 4618457 x + 133472, r2 = 0.99). Standard sample containing precocene I (1 mg/mL) and precocene II (1 mg/mL) obtained from Sigma (St Louis, MO, USA) were prepared in methanol. Identified precocene I was screened against Trypanosoma evansi for trypanocidal activity on Vero cells grown in Dulbecco’s Modified Eagle Medium (DMEM) and supplemented with foetal calf serum (FCS) 20-40% at appropriate conditions. In vitro cytotoxicity test of precocene I at concentrations (1.56-100 µg ml-1) was done on Vero cells but without FCS. In vitro trypanocidal activity varied from immobilization, reduction and to the killing of trypanosomes in corresponding ELISA plate wells. At 250 µg ml-1of purified precocene I, there was drastic reduction of average mean trypanosomes count to complete killing of trypanosomes (40.±0.0 to 0.00±0.00) at 9 h of incubation, which was statistically the same as diminazine aceturate (50 µg ml-1) at 4 h. Trypanosomes counts decreased in concentration and time –dependent manner with significant difference (P \(\) 0.05 to 0. 01)). During in vitro cytotoxicity test, Purified precocene I and diminazine aceturate standard drug, were cytotoxic to Vero cells at all concentrations except at concentrations of 6.25-1.56 µg ml-1 and 1.56 µg ml-1, respectively. Precocene I was responsible for higher anti-trypanosomal activity. Precocene I could be near future trypanocidal compound for a new trypanocide. To attest its full and firm trypanocidal activity potential, in vivo test need to be conducted alongside the in vitro method.